Redes de saúde e (m) desastres: cartografias da resiliência em Santa Maria - RS - Hinterholz, Lisiane Bernhard (2018)
The disaster in the night club “Kiss” happened in January of 2013. Since, technologies and protocols have been published. This research explores characteristics of the services network and of the management that help or produce barriers to the facing of big dimension disasters. The goals of the investigation were “to cartograph” the making of healthcare networks to face the effects of the disaster in the night club Kiss in Santa Maria, Rio Grande do Sul; register ideas that oriented the production of healthcare networks to attend the victims of the Kiss club disaster; mapping the main points of attendance and (in) it’s (dis)articulations; identifying the initial conditions and decisions that contributed to the resilience of the healthcare network of Santa Maria; propose strategies/hints so that caring networks can respond to the emergencies and grant continuity of the care in situations of disaster. Are highlighted the characteristics of immediate care, the creation of new points in the network and the management of a public hospital. Methodology: this is a qualitative, participative investigation, with characteristics of the Fourth Generation Evaluation associated to the cartographic method. The main sources of information are individual and collective interviews with representatives of groups with distinctive interests in the proposed theme. Highlighted themes were placed once again in the talk and took part in interviews with the remaining representatives. Six interviews and one focal group were made. These were transcribed and analyzed, generating a text with the narrative of assistance in the disaster and another with the categories Importance of SUS, network management and longitudinal care. Results: the initial confrontation depends more on the capacity of mobilization, connectivity and community resources. The attendance to the victims demands vision of complementarity (in the multi-professional work and in the network) and the opening to less hierarchic forms of service management (already existent or new). The work of many fronts, the negotiation with representatives from many spheres of the government, the entry of the private and corporate interests, the inclusion of different theoretical perspectives, the participation of volunteers and the protection facing the press offensive demanded methodologies of institutional support and other, more democratic, forms of management. Experience in co-management was an important facilitator. The inexistence of public services is the barrier to the immediate assistance and the frailty of the basic care limits the longitudinal care. Concearning the public hospital, new forms of management emerged, composing the Universidade Federal de Santa Maria, Rio Grande do Sul, coordinators and assistance teams. Characteristics of more democratic management do not stand after the crisis and the experience is not utilized to face day-to-day scenarios.